ETIKA KOMUNIKASI GURU DALAM PLATFORM DIGITAL: ANALISIS PERLINDUNGAN DAN PEMBINAAN KARAKTER PESERTA DIDIK - Chasanah, Faiqotul; Lailatun Nadhifah, Shinta; Iva Faulina, Cantika; Muhlisin, Muhlisin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of digital technology in the Industry 4.0 era has transformed communication patterns in education, including interactions between teachers and students through digital platforms. This transformation requires the application of communication ethics that not only support learning effectiveness but also ensure the protection and character development of students. This study aims to analyze the principles of teachers’ communication ethics in digital platforms, their contribution to student protection, and their role in character building. This research employs a library research method with a descriptive qualitative approach. The data were obtained from various secondary sources such as scientific journals, books, and educational policy documents, and were analyzed using content analysis techniques. The results indicate that teachers’ communication ethics in digital platforms are essential in maintaining professionalism. Principles such as responsibility, privacy protection, respectful communication, and the wise use of digital media play a significant role in protecting students from negative impacts. Furthermore, ethical communication supports character development through role modeling and the habituation of moral values. Therefore, a comprehensive digital code of ethics for teachers is needed to support safe, integrity-based, and character-oriented educational practices